2019
DOI: 10.1080/17457823.2019.1683756
|View full text |Cite
|
Sign up to set email alerts
|

Ethnography, materiality, and the principle of symmetry: problematising anthropocentrism and interactionism in the ethnography of education

Abstract: In this article we draw on actor-network theory (ANT), an established branch of a broader approach to social and interpretivist inquiry that is described in terms of sociomaterialism, relational materialism or material semiotics, in order to challenge the methodological and empirical orthodoxies of anthropocentrism and interactionism that have for a long time informed dominant discourses of ethnographic work. We draw on paradigmatic concepts from ANT to open up new possibilities for understanding education pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The discussion of the results we have obtained reflects and also adds to our earlier discussion of the history of ethnography in the early parts of the article and in earlier articles (Beach, 2010b; Larsson, 2006; Tummons & Beach, 2020). This history suggested that both ‘globally’ and nationally ethnography in education research is a methodology that is generally in constant flux, but that also exhibits relatively short periods of local stability in terms of the common markers of method, which may then become future suturing criteria for the identity of ethnographic work.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The discussion of the results we have obtained reflects and also adds to our earlier discussion of the history of ethnography in the early parts of the article and in earlier articles (Beach, 2010b; Larsson, 2006; Tummons & Beach, 2020). This history suggested that both ‘globally’ and nationally ethnography in education research is a methodology that is generally in constant flux, but that also exhibits relatively short periods of local stability in terms of the common markers of method, which may then become future suturing criteria for the identity of ethnographic work.…”
Section: Discussionsupporting
confidence: 60%
“…The turn was then generally followed by an initialising period of consolidation, a period of quantitative take off and later some diversification (Beach, 2010b; Beach et al, 2018; Casimiro Lopes & de Lourdes Rangel Tura, 2018; Eisenhart, 2018; Hammersley, 2018). Growth and diversification can threaten existing research identities and hegemony in a field of course, which some members of the research community may experience as rather challenging and may resist (Sieber Egger & Unterweger, 2018; Tummons & Beach, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Should we include or ignore those human actors who are not 'academic'? Ought the quality of 'academic' be ascribed primarily to people, effectively maintaining an anthropocentric interactionist standpoint, or should it always be ascribed to the non-human as well as human actor, thereby foregrounding the principle of symmetry (Tummons and Beach, 2019)?…”
Section: Some Conclusion: Academic Work Is Never Only Done By Academicsmentioning
confidence: 99%
“…changing societal expectations (see Tummons and Beach 2020), what is often lost is attention to universities' civic responsibilities and education for the 'public good' (Giroux 2010). This arguably involves supporting people to participate meaningfully in society (see Altbach et al 2009;Giroux 2010) and contributing to the creation of a society worth participating in (Kemmis et al 2014).…”
mentioning
confidence: 99%